The consequences of an ADHD-score in the clinical range in adolescence for mental health in young adults. - Haldorsen, Andreas (UiT Norges arktiske universitet, 2019)
Klarer ikke gjennomføre sak: Failed to perform step 2 in Navigate Stage 'Select All' on page 'Read PDF' - Access is denied Objectives To investigate the consequences of ADHD symptoms in adolescence to mental health as young adult, in a Norwegian population. Design and setting Data were obtained from the Norwegian Arctic Adolescent Health Study, a school-based survey conducted among 10th grade students in North Norway (2003-2005). This data were linked to the Norwegian Patient Registry(2008-2012). Participants In total, 3987 (68%) of all 5877 invited participants consented to the registry linkage. Methods The questionnaire in this study included many different subject areas, physical health, living conditions, life events, and sociodemographic relations, and it also included the Strength and Difficulties Questionnaire (SDQ). Based on the SDQ the symptom score «very high» was combined with the impact score “very high” to define an ADHD-group within the clinical range (n=94). This group was compared to a control group (n=3893) consisting of all the participants that did not qualify for the ADHD-group with scores in the clinical range. Results The findings in this study suggest that the group with scores in the ADHD clinical range are significantly more likely to suffer mental health problems later in life. All the included variables indicate statistically significant differences between the two groups compared. Conclusion The group of participants in this study defined in an ADHD-group within the clinical range are found to have statistically significant higher risk in all the examined variables compared to the control group.